2017
DOI: 10.17576/mjas-2017-2101-22
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Characterization of Oil Palm Empty Fruit Bunch

Abstract: The interest in Oil Palm Empty Fruit Bunch (OPEFB) as a promising feedstock for bioconversion into value added products is growing fast, thus a thorough analysis of its component becomes necessary. In this study, the biomass chemical composition and physical feature of OPEFB was analysed to explore and understand the potential of OPEFB as bioconversion feedstock. National Renewable Energy Laboratory (NREL) standard protocols were used to characterize and determine the chemical composition of OPEFB. Through thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…As observed, silica bodies were discovered embedded on the fiber surfaces and substances such as oil and impurities that covered the surface. This result was comparable to the findings of Ibrahim et al that reported the presence of silica bodies on the surface of untreated fibers [26,27]. The alkaline treatment substantially changed the morphology of the fibers (Figure 1(b)).…”
Section: Morphology Analysissupporting
confidence: 91%
“…As observed, silica bodies were discovered embedded on the fiber surfaces and substances such as oil and impurities that covered the surface. This result was comparable to the findings of Ibrahim et al that reported the presence of silica bodies on the surface of untreated fibers [26,27]. The alkaline treatment substantially changed the morphology of the fibers (Figure 1(b)).…”
Section: Morphology Analysissupporting
confidence: 91%
“…Other than that, oil palm empty fruit bunches can also be used as biofertilizer because it contains bacteria that can bind nitrogen and phosphate solvents (Hoe et al 2016), as degraders lignin bacteria (Tahir et al 2019), as organic materials decomposers (Chin et al 2017), as well as a fuel for power plant (Han and Kim 2018). Oil palm empty fruit bunches also contain abundant bacteria, high cellulose so it can be used as a source of bacterial energy for the biosynthesis process (Md Yunos et al 2015;Rosli et al 2017). Moreover, Rosli et al (2017) found that the oil palm empty fruit bunches contain the polymeric carbohydrates such as cellulose and hemicellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Oil palm empty fruit bunches also contain abundant bacteria, high cellulose so it can be used as a source of bacterial energy for the biosynthesis process (Md Yunos et al 2015;Rosli et al 2017). Moreover, Rosli et al (2017) found that the oil palm empty fruit bunches contain the polymeric carbohydrates such as cellulose and hemicellulose. Also, the oil palm empty fruit bunches fiber was made up of 31.4% of glucan, 18.6% xylan and 2.7% arabinan with the lignin accounted for around 23.9%.…”
Section: Introductionmentioning
confidence: 99%
“…With the heat-treated EFB, the vibration peaks at 2362.45 cm −1 weakened, thus concluding that the amounts of hydroxyl, hemicellulose, and cellulose were reduced when the EFB were exposed to the heat treatment [ 36 ]. The C=C stretching of the aromatic ring of lignin in untreated EFB at 1425.13 cm −1 was reduced to 1372.36 cm −1 after heat treatment, indicating the loss of lignin [ 37 ]. Thus, removing lignin, hemicellulose, and cellulose from heated samples led to the decreasing peak intensity in the spectra.…”
Section: Resultsmentioning
confidence: 99%